Experimental investigation of heat removal factor in solar flat plate collector for various flow configurations. Issue 4 (16th March 2017) - Malvi, C. S.; Gupta, Arpit; Gaur, M. K.; Crook, R.; Dixon-Hardy, D. W.
ABSTRACT: This paper reports the performance of a solar flat plate collector for various flow configurations and presents a comparative evaluation. Three cases have been discussed: (i) serpentine flow, (ii) parallel-wall-to-wall flow, and (iii) spiral flow. The heat removal factor ( FR ) is the ratio of the actual heat transfer to the maximum possible heat transfer through the collector plate. A special case showing the effect of phase change material (PCM) on FR in the case of serpentine is discussed. A sheet-and-tube type collector where the tubes are bonded to the absorber plate by a suitable adhesive is considered. Equations showing the dependence of FR on the fin factor were studied and indoor experiments were conducted to determine the value of FR . Finally, a numerical investigation was done and comparisons were evaluated. Results indicate that when the mass flow rate ( ) of water is 1, the value of FR for serpentine and parallel wall-to-wall flow is 0.44 and 0.88, respectively. It was also observed that for the case of PCM, FR is a variable quantity and its value ranges from 0 to 0.28. In this case, FR is a function of the PCM melting and solidifying phases rather than mass flow and is proportional to the melting temperature of the PCM. Also, it is observed that in a conventional water heater with serpentine flow or parallel wall-to-wall flow, the value of FR does not increase significantly beyond a mass flow rate ( ) of 4 kg/hr.